WHAT ARE THE PREFERRED BLOOD PRESSURE MEASUREMENT METHODS BY DOCTORS TO DETECT, DIAGNOSE AND TREAT HYPERTENSION? A SURVEY STUDY IN A CHINESE POPULATION. (April 2021) - Lee, Kam Pui; Choi, Ryan Chun Ming; Liu, Licheng; Yip, Benjamin Hon-Kei; Gao, Ting; Wong, Samuel Yeung-Sha
Abstract : Objective: Hypertension(HT) is the most common chronic disease and is the leading cause of morbidity and mortality. Its detection, diagnosis and management depend heavily on accurate blood pressure(BP) measurement. It is recommended that the diagnosis of HT should be confirmed or assisted by out-of-office BP measurement, including ambulatory BP measurement(ABPM) and home BP measurement(HBPM). When office BP is used, automated BP measurement(AOBP), which automatically provides an average of 3–5 BP readings, is preferred. This study aimed to describe the BP measurement methods used by doctors working in primary care to detect, diagnose and treat hypertension. Design and method: This is a cross-sectional survey. All doctors registered in the "Primary Care Directory" were mailed a questionnaire, asking their preferred methods to detect, diagnose and treat hypertension. Furthermore, the number of BP readings they usually obtained on office BP or HBPM to diagnose or manage HT was asked. Results: Four hundred and forty-five doctors responded. Manual measurement by a mercury or aneroid devices was the commonest method to detect(63.1%), diagnose(56.4%), and manage(72.4%) HT. There was an underuse of ABPM and only 1.6% of doctors used ABPM to diagnose HT. 22.2% of doctors used HBPM to diagnose HT; and 56.8% of doctors used HBPM to manage HT. A quarter (26.7%) of participants only obtained one BP reading when they used office BP. Only 40% of participants obtained at least 12 BP readings when HBPM was used. Doctors who obtained specialist qualification in family medicine were more likely to use AOBP in clinics and to obtain enough office BP readings for diagnosis and management of HT. Conclusions: Doctors in primary care in Hong Kong prefer to use manual office BP, especially mercury or aneroid devices, to screen, diagnose and treat HT. There is an underuse of AOBP and out-of-office BP. Studies are needed to understand the underlying reasons and to minimize the gap between real-life clinical practice and scientific advances.